Pembangunan Perumahan Layak untuk Kesejahteraan Masyarakat (Studi Kasus Rusunawa Keputih Surabaya) - Arinda Septiani (JIP ( Jurnal Industri dan Perkotaan ), 2022)
Infrastructure development is the main step to improve the welfare of a city. With an adequate infrastructure, education, health, social and economic aspects will work well and produce positive outcomes. One of the problems experienced by most big cities is poverty. The higher the poverty rate, the lower the percentage of community welfare in a city. The resulting impact will be an increase in the number of crime in a city. Article 28H paragraph (1) has explained that every individual has the right to a decent life by getting a decent place to live. One of the efforts made by the Surabaya City Government to improve infrastructure is to utilize land for the construction of Rusunawa for the poor and those who don’t have a place to live. Currently, almost 20 rusunawa have been built in the city of Surabaya, one of them is in the Keputih area. Here the author is interested in examining how the impact felt by the people of Surabaya in responding to the efforts of the City Government. The method used by the author uses is  observation and in-depth interviews with the residents of the Keputih flats. The theoretical basis used by the author is based on the theory of several previous researchers, so that it can be analyzed with the results of conditions in the field. The results of this study indicate that the Surabaya City Government has succeeded in building Rusunawa in accordance with Law no. 20 of 2011 regarding flats, that received a positive response and give a good impact for the Surabaya City Community.